Anatomy of a 'suspended' seafloor in the dense brine waters of the deep hypersaline Urania Basin. (January 2020) - Aiello, I.W.; Beaufort, L.; Goldhammer, T.; Heuer, V.B.; Hinrichs, K.-U.; Zabel, M.
Abstract: When micron-sized particles are suspended into the dense brine waters of a deep hypersaline basin, in the absence of biological packaging, their settling velocities should be greatly attenuated. We observed this phenomenon in the anoxic brine water of the Urania Basin in the eastern Mediterranean. We found that the deepest part of this basin is filled with a high-density, about 110 m thick, homogenous fluid mud layer mainly containing microfossils of coccoliths and nannoplankton of Pleistocene and Pliocene age that float in a hot methane-laden brine overlaid by a 'clear' brine. The top of the fluid mud forms a secondary 'suspended seafloor' that has been stable for at least the last two decades since the discovery of the basin. The geochemical characteristics of the fluid mud (e.g. lower salinity than the clear brine, methane-rich) point to a deep source for the fluids, while the age of the microfossils suggests that the floating biogenic particles came from shallower, post-Messinian pelagic deposits such as those exposed along the walls and the rim of the Urania Basin. We hypothesize that catastrophic gravity failures and mass mobilization of the post-Messinian sedimentary layers triggered by earthquake activity are one of the main sources of the sediment in the fluid mud. Because of both, the dense brine fluids, the continuous mixing by thermal convection and the very fine grained nature of the particles, the re-mobilized sediments have never settled, and stay suspended as if they were frozen in time. The prolonged residence time of the supersaturated fluids and the associated microbial activity have also fostered the precipitation of the authigenic gypsum crystals and micron-sized authigenic carbonates that occur mixed with the fluid mud sediments.